Melanchthon y los aristotelismos protestantes. El caso de los comentarios a la Ética y la Política - Svensson, Manfred (Cauriensia, 2024)
Contrary to what is suggested by the myth of a radical break, the Aristotelian tradition of practical philosophy was widely cultivated in early Protestantism. Recognition of this fact, however, often goes hand in hand with a monolithic reduction of Protestant Aristotelianism to its Melanchthonian origins. The present article seeks to make Charles Schmitt’s attention to the multiplicity of Renaissance Aristotelianisms fruitful for the case of the Protestant commentators of Aristotle, thus offering a more precise view of Melanchthon’s place in that tradition.